2018
DOI: 10.4314/tjpr.v17i4.9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of natural growth promoters on immunity, and biochemical and haematological parameters of broiler chickens

Abstract: Purpose: To investigate the efficacy of promising alternatives to antibiotic growth promoters (organic acids, phytobiotics, and their combinations) as feed additives in poultry feed. Methods: Different feed treatments were formulated with organic acids, phytobiotics and their combinations, and their effects on blood profile, serum enzymes and immunity parameters were evaluated in broilers at 21 and 42 days of age. Results: Cholesterol, triglyceride and HDL levels of the 21-and 42-day old broilers were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
3
21
0
Order By: Relevance
“…The incorporation of 0.25% of C. longa powder significantly increased white blood cell, hematocrit, lymphocyte, monocyte, granulocyte and platelet concentration. This study corroborates with the work of Sey et al [17] who showed that phytobiotics are also used as blood and immunity purifiers because they stimulate white blood cells and eventually increased interferon levels. However, our results contradict those of Sara et al [18] who found that phytobiotics did not have a significant effect on these blood parameters.…”
Section: Discussionsupporting
confidence: 92%
“…The incorporation of 0.25% of C. longa powder significantly increased white blood cell, hematocrit, lymphocyte, monocyte, granulocyte and platelet concentration. This study corroborates with the work of Sey et al [17] who showed that phytobiotics are also used as blood and immunity purifiers because they stimulate white blood cells and eventually increased interferon levels. However, our results contradict those of Sara et al [18] who found that phytobiotics did not have a significant effect on these blood parameters.…”
Section: Discussionsupporting
confidence: 92%
“…Similar findings in another study were reported by Krauze et al [ 50 ], who studied the dietary effects of probiotic Bacillus subtilis (0.25 g/L) Enterococcus faecium (0.25 g/L), and phytobiotics containing cinnamon oil (0.25 mL/L) in broiler chickens and found improvements in the immune system and parameters such as RBCs and Hb. In another experiment, Gilani et al [ 11 ] examined the efficacy of organic acids and phytobiotics (possessing flavonoids) in poultry feed as alternatives to AGPs, observing significant increases in RBC and WBC counts, as well as an increase in PCV in broiler chickens. Similarly, broiler chickens fed Garden cress ( Lepidium satvium ) seed powder [ 51 ], cayenne pepper ( Capsicum frutescens ) and turmeric ( Curcuma longa ) powders [ 52 ], and pawpaw leaf and seed meal [ 53 ] showed increased values of Hb, PCV, and RBCs.…”
Section: Discussionmentioning
confidence: 99%
“…Herbs have shown positive effects on the performance and biological health of broiler chickens [ 9 , 10 ], can improve haematological blood indicators and serum biochemical attributes [ 11 , 12 , 13 ], and have also been reported to regulate the kidney and liver functions [ 14 , 15 ]. Among such herbs, Persicaria odorata , of the family Polygonaceae, is of important significance.…”
Section: Introductionmentioning
confidence: 99%
“…Misuse of antibiotic drugs can cause drug resistance bacteria and antibiotic residue in animal products (Costa et al, 2007); therefore, natural antimicrobial products have been considered as indispensable resources (Ferrini et al, 2008). It has been shown that the use of antibiotic growth promoters among the poultry feed have been banned since 2006, although they play a beneficial role in growth performance and disease prevention among the broiler chickens by developing resistance in bacteria and presence of drug residues in meat (Gilani et al, 2018). The feed grade antibiotic growth promoters have been banned due to cross-resistance and the risk of possible drugs multiple resistances in human pathogenic bacteria.…”
Section: Introductionmentioning
confidence: 99%